WAYS TO OPTIMIZE COSTS AND PRODUCT COST IN MANUFACTURING ENTERPRISES - Nematjonova Risolatxon Dilshodbek qizi, (TADQIQOTLAR, 2026)
Abstract This article examines the classification of production costs, the mechanisms of product cost formation, and modern methods for their optimization in manufacturing enterprises. In the context of a market economy, the issues of reducing product costs, using resources efficiently, and implementing modern management technologies (Lean production, Kaizen, KPI) to increase the competitiveness of enterprises are analyzed. Furthermore,  cost  productivity  is  demonstrated  through  practical  calculations  and mathematical-economic models.